Development, characterization and performance evaluation of a swelling resistant membrane for CO2/CH4 separation - Suleman, M.S. (Elsevier B.V., 2018)
Swelling in polymeric membranes due to the humid feed is a major issue in gas separation applications at offshore conditions. To ensure the integrity of the polymeric membrane, a high capital cost dehydration system is typically installed together with the membrane system. Hence, to minimize the dehydration requirement, a swelling resistant membrane was developed by film casting of polydimethylsiloxane (PDMS) over polysulfone (PSF). The PSF/PDMS composite membrane exhibited higher contact angle as compared to PSF membrane. Performances of the developed membranes were evaluated with and without water in the feed gases at the pressure of 2â10 bar. Separation performance in the PSF membrane was affected by swelling in the membrane; however, the composite membrane with the PDMS film resisted the water swelling in membrane and CO2/CH4 selectivity increased from 21.6 to 27.7 at 10 bar. Under wet feed conditions, the PSF/PDMS composite membrane exhibited stability for 24 h with stable permeance and selectivity. Based on the permeation results and the stable performance of a PSF/PDMS membrane, it can be concluded that the developed composite membrane demonstrates a potential to be used in an offshore membrane system with the minimum dehydration requirement for CO2/CH4 separation. Â© 2018 Elsevier B.V.